Pengaruh Isoflavon terhadap Kadar Trigliserida pada Wanita Pascamenopause - Ryski Ludmilla (STIKes Ibnu Sina Ajibarang, 2025)
Isoflavones are compounds found in certain foods such as soy and may be used to reduce triglyceride levels in postmenopausal women. This meta-analysis aims to combine findings from multiple studies, with varying sample sizes, to gain a deeper understanding of the effects of isoflavones on changes in triglyceride levels in postmenopausal women. A literature search was conducted through electronic databases such as Google Scholar, PubMed, and Science Direct. The results of a meta-analysis of 10 research literatures showed that isoflavone administration had an impact on significantly reducing blood triglyceride levels in postmenopausal women under 65 years of age.